‘Close to the city centre, close to the university’. Are there symptoms of studentification in Gdańsk, Poland? - Grabkowska Maja; Frankowski Jan (Bulletin of Geography. Socio-Economic Series, 2016)
Students are increasingly recognised as important actors of urban change in contemporary cities. The article presents an analysis of incipient studentification processes in Gdańsk. Its general aim is to reveal patterns of students’ presence and activity which translate into spatial and socio-economic transformations of a post-socialist city at the level of neighbourhoods. The study consists of a survey on students’ residential behaviour, complemented by field and desk research. According to the results, due to the fact that Polish students’ housing and lifestyle choices are limited by their low purchasing power, student-dedicated services have a rather negative impact on the quality of urban space. Furthermore, under these conditions studentification may not be regarded as a stimulus to the gentrification process, which is rather driven by hipsters and affluent foreign students.